Pilates and Pelvic Tilt Reduce Back Pain in Trimester III Pregnancy - Annisa Adenikheir; Yelva Febriani (Maternal Child Health Care, 2023)
Pain is one of the problems often experienced by pregnant women in the third trimester. The phenomenon of pain is one of the complaints that almost 70% experienced by pregnant women in the world. The pain experienced by pregnant women can interfere with daily activities and interfere with activities such as sleep.This study aims to determine the effect of pilates gymnastics and pelvic tilt exercises on back pain experienced by third trimester pregnant women.This type of research uses a Quasi Experiment design with a one group pretest-posttest method. The total population of pregnant women is 25 people with a sample of 10 people. The study was conducted for 3 weeks.Univariate analysis showed that 10 of the samples had an average of 6,50 pre-intervention pain with a minimum pain of 6 to a maximum of 7. And on average after administration of 3,60 intervention with minimum pain 3 and maximum 4.It was concluded that there was an effect of pilates gymnastics and pelvic tilt exercises on back pain in third trimester pregnant women.Keyword : Pilates gymnastic, Pelvic tilt, Back Pain, Pregnant Women